Development of media EDUMEDIG with the model problem-based learning to improve science understanding - Ariyanti, Mei Riska Dwi; Sulianto, Joko; Buchori, Achmad (Indonesian Journal of Educational Development (IJED), 2025)
This Research and Development (R&D) study was conducted to evaluate the feasibility (validity and practicality) and efficacy of the Problem-Based learning Interactive Game Educational Media (EDUMEDIG) in enhancing the understanding of Science and Social Sciences among fifth-grade elementary students. The core problem addressed was the limited use of interactive conventional media, which contributed to student passivity, lack of enthusiasm, and difficulties in grasping Science material. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) guided the development process. Using a quasi-experimental Pretest-Posttest Control Group Design, the study's population comprised all fifth-grade students. Sampling was carried out using a purposive sampling technique, selecting 31 students from SD N Sambiroto as the experimental group and 30 students from SD N 2 Mojosari as the control group. Data collection techniques involved written tests (pre-test and post-test) to measure effectiveness, and questionnaires (expert validation, teacher, and student responses) served as the research instruments to assess feasibility. The findings demonstrate that the EDUMEDIG media has excellent validity (Media Experts: 95%; Material Experts: 92.5%) and very high practicality (Teachers: 98.3%; Students: 100%). Crucially, the media proved highly effective, as confirmed by a T-Test result of 0.000 (<0.05), indicating a significant difference in mean scores between the two groups. This effectiveness was further underscored by the experimental class's N-Gain score of 0.71 (High category), which was substantially higher than the control group's score of 0.257 (Low category). In conclusion, the EDUMEDIG media successfully serves as a valid, practical, and effective innovative solution. It is recommended that this EDUMEDIG media be implemented as a proven tool to enhance students' motivation, engagement, and conceptual understanding in IPAS (Integrated Science and Social Sciences) subjects.